2015
DOI: 10.1016/j.clim.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol, a Chinese herbal compound, controls autoimmune inflammation by altering the balance of pathogenic and regulatory T cells in the target organ

Abstract: Inflammation is an integral component of autoimmune arthritis. The balance of pathogenic T helper 17 (Th17) and protective T regulatory (Treg) cells can influence disease severity, and its resetting offers an attractive approach to control autoimmunity. We determined the frequency of Th17 and Treg in the joints of rats with adjuvant arthritis (AA), a model of rheumatoid arthritis (RA). We also investigated the impact of Celastrol, a bioactive compound from the traditional Chinese medicine Celastrus that can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 32 publications
(46 reference statements)
2
95
0
Order By: Relevance
“…Celastrol, derived from a traditional Chinese herb celastrus, has anti-inflammatory and anti-oxidant properties [35,37]. We have previously shown in the AA model that celastrol possesses anti-arthritic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol, derived from a traditional Chinese herb celastrus, has anti-inflammatory and anti-oxidant properties [35,37]. We have previously shown in the AA model that celastrol possesses anti-arthritic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol is a herb found in numerous regions of China, with extensive pharmacological effects (10). Celastrol is a pentacyclic triterpene monomer extracted from the root of Tripterygium wilfordii.…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol has been studied for the treatment of asthma, skin inflammation, arthritis, systemic lupus erythematosus, hypertension, and neurodegenerative disorders [167]. Recent data has shown that celastrol inhibits NF-κB pathway leading to a significant reduction in the expression of IL-6 and IL-1β in myeloid cells [168]. Clinical investigation of this natural compound has identified a number of health benefits including anti-oxidant, anti-cancer, and anti-inflammatory properties [169].…”
Section: Natural Anti-inflammatory Compounds To Modulate Inflammatmentioning
confidence: 99%